Atypical clinical presentation mimicking stroke in an adult patient caused by a rare diffuse leptomeningeal glioneuronal tumour - Stapińska-Syniec, Angelika; Gogol, Anna; Acewicz, Albert; Sobstyl, Michał; Wierzba-Bobrowicz, Teresa; Grajkowska, Wiesława (Polish Journal of Pathology, 2022)
A diffuse leptomeningeal glioneuronal tumours (DLGNT) are very rare tumours of the central nervous system, typically characterized by enhancement of subarachnoid space with cystic lesions, diffuse leptomeningeal infiltration, and no primary mass. We report an atypical clinical presentation of DLGNT. A 48-year-old male was admitted to hospital with symptoms of ischaemic stroke. Magnetic resonance imaging of the head revealed contrast enhancement of the meninges and other parts of the brain. A stereotactic frame biopsy was performed on the patient, which revealed the DLGNT. Diffuse leptomeningeal glioneuronal tumours are mostly seen in individuals less than 18 years old and are characterized by slow growth and low-grade histological appearance. Diffuse leptomeningeal glioneuronal tumours can be aggressive in adults.